2009
DOI: 10.3171/2008.8.jns17650
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for convexity meningiomas

Abstract: Object Meningiomas of the cerebral convexity are often surgically curable because both the mass and involved dura mater can be removed. Stereotactic radiosurgery has become an important primary or adjuvant treatment for patients with intracranial meningiomas. The authors evaluated clinical and imaging outcomes in patients with convexity meningiomas after radiosurgery. Methods The patient cohort consisted of 125 patients with convexity meningiomas managed using radiosurgery at some point during an 18-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 23 publications
0
44
0
1
Order By: Relevance
“…6,7,9,10,15,18,19,29,31,42,44,50 Therefore, the new onset of any of the aforementioned complications in each patient following SRS was documented and analyzed. The development of any new T2 or FLAIR signal changes surrounding the lesion following SRS were interpreted as edema.…”
Section: Analyzed Variablesmentioning
confidence: 99%
“…6,7,9,10,15,18,19,29,31,42,44,50 Therefore, the new onset of any of the aforementioned complications in each patient following SRS was documented and analyzed. The development of any new T2 or FLAIR signal changes surrounding the lesion following SRS were interpreted as edema.…”
Section: Analyzed Variablesmentioning
confidence: 99%
“…Kondziolka et al, reported peritumoral imaging changes in 5% either due to edema or adverse radiation effects and an overall complication rate of 9.6% in their series of convexity meningiomas [14].…”
Section: Discussionmentioning
confidence: 98%
“…Adopting the concept of clinical improvement as the resolution of neurological symptoms, and/or increased pre-operative performances, the vast majority of cases shows stable or improved KPS and neurological gradings at 5-7 years or longer FU. A recent review published by the Pittsburgh Gamma Knife Center (39,40) confirms in a cohort of 972 patients, with a long term follow up (for some of them up to 20 years) an overall tumor control rate up to 97% a definitively low overall morbidity rate (7.7%) slightly higher for crucial locations such as the cavernous sinus and petroclival region.…”
Section: Gamma Knife Radiosurgerymentioning
confidence: 99%
“…the most biologically justified -targeting dose-volume in these peculiar lesions, is still a matter of debate, with a spectrum of options: from including "only" the gross, T1 contrast enhancing tumor, plus a supposedly infiltrated margin of a few mm (39,40,50), up to the controversial inclusion either of the "dural tail", or of the hyperostotic bone. However, the former -according to extremely refined studies -has been shown to be essentially composed by hypervascular dura with surprisingly none of the expected tumor colonies (34).…”
Section: Gamma Knife Radiosurgerymentioning
confidence: 99%
See 1 more Smart Citation